THE EFFECT OF A SINGLE OR FRACTIONAL DOSE OF LOCAL ANESTHETIC ON HEMODYNAMICS IN EPIDURAL ANESTHESIA EVALUATED ACCORDING TO EJECTION FRACTION - Arik, Hasan; Erhan, Omer L.; Bestas, Azize; Ozer, Ayse Belin; Yildizhan, Ozden (Gunes Kitabevi Ltd Sti, 2012)
Introduction: The purpose of our study, was to investigate the effects of LA given in a single or fractioned dose on hemodynamics during epidural anesthesia applied to risky patients. Materials and Method: 80 patients of 50 years or above age who were to receive TUR-P surgery, who were in ASA III-IV group were included in the study. They were first divided into 2 groups according to their EFs, then further subdivided into 4 groups of 20 individuals according to two different application methods of the LA, being single dose and fractional. Hemodynamics of the patients were recorded continuously during the intervention. Results: The change in hemodynamic parameters of the patients was found to be more pronounced in the group with lower EF. What's more, among patients with low EF, it was observed that the decrease in hemodynamic parameters started later and lasted shorter in the group received fractional LA. Conclusion: The fast developing sympathetic block after application of a single dose of LA cannot be compensated in patients with low cardiac reserve and the consequences can be serious. It was concluded that the fractioned application of LA during epidural anesthesia in the old patient with cardiac risks may progress more stable in relation to haemodynamics.
Keywords: Anesthesia, Epidural; Stroke Volume; Hemodynamics; Anesthetics, Local